Flame retardancy of Scots pine (Pinus sylvestris) by using polyethylene glycol 400 and phosphoric acid - Brahmia, Fatima Zohra (International Journal of Psychosocial Rehabilitation, 2020)
Wood is natural material that can be used in many fields because it has good mechanical properties and easy to work with but its resistance to fire considered weak. Fire resistance is an important material characteristic in many applications. For this reason, a lot of research made on this topic for finding solutions in both physical and chemical ways, to increase fire resistance.This study presents experiments for improving the fire resistance of scots pine (Pinus sylvestris) by using Polyethylene glycol 400 and phosphoric acid as fire retardants. The investigation was made by using the single flame source test as fire test according to the standard (EN ISO 11925-2:2011). In addition, contact angle was measured to calculate the surface energy, surface polarity and wettability in order to give a better understanding to the used fire retardants and there effect on the surface of Scots pine. Results showed that Polyethylene glycol 400 and phosphoric acid are effective as fire retardants in case of a high dose of phosphoric acid and minor time in the microwave.